2009
DOI: 10.1128/mcb.00383-09
|View full text |Cite
|
Sign up to set email alerts
|

Repression of ESR1 through Actions of Estrogen Receptor Alpha and Sin3A at the Proximal Promoter

Abstract: Gene expression results from the coordinated actions of transcription factor proteins and coregulators. Estrogen receptor alpha (ER␣) is a ligand-activated transcription factor that can both activate and repress the expression of genes. Activation of transcription by estrogen-bound ER␣ has been studied in detail, as has antagonist-induced repression, such as that which occurs by tamoxifen. How estrogen-bound ER␣ represses gene transcription remains unclear. In this report, we identify a new mechanism of estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 73 publications
11
89
1
Order By: Relevance
“…E2-ER, as with other transcription factors, also represses the expression of genes. Although the mechanisms are unclear, recruitment of corepressor complexes or squelching of coactivators by the ERE-bound E2-ER is suggested to induce chromatin modifications that counteract the effects of activating signals, thereby repressing the gene expression (27,28). Our results demonstrate that PV mirrored the ability of E2-ERα to regulate the transcription of responsive genes that rely on EREinteractions.…”
Section: Discussionmentioning
confidence: 55%
“…E2-ER, as with other transcription factors, also represses the expression of genes. Although the mechanisms are unclear, recruitment of corepressor complexes or squelching of coactivators by the ERE-bound E2-ER is suggested to induce chromatin modifications that counteract the effects of activating signals, thereby repressing the gene expression (27,28). Our results demonstrate that PV mirrored the ability of E2-ERα to regulate the transcription of responsive genes that rely on EREinteractions.…”
Section: Discussionmentioning
confidence: 55%
“…ERa binding sites have been identified in the ERa gene promoter B, as well as in upstream enhancer regions (Carroll et al 2006). Consistent with this, it has been shown that ERa can regulate its own expression (Castles et al 1997, Ellison-Zelski et al 2009). Under normal physiological conditions, expression of ERa and estrogen levels are inversely related and repression of the ERa promoter by recruitment of ERa upon estrogen stimulation has been reported (Ellison-Zelski et al 2009).…”
Section: Introductionsupporting
confidence: 52%
“…If that happens, an overexpression of ERα, which is the product of ESR1 gene might result and it relates to increase in the risk of breast cancer among people with A allele compared to people without A allele. As suggested by other studies, a higher level of ERα is related to the uncontrolled proliferation of breast cells (Ellison-Zelski et al, 2009).…”
Section: Discussionmentioning
confidence: 62%